Problem of the Teacher in Lithuania (1918-1940) - Karčiauskienė, Magdalena (Acta Paedagogica Vilnensia, 1993)
The Republic of Lithuania established in 1918 had to face the education system that was completely degraded during the World War I. There were few schools, their material conditions were extremely poor. Expanding the network of schools, improvement of existing schools in order to meet the needs of the times has been the main task of the reform of Lithuanian education system. One of the main conditions for successful school reform – education and training of professional, dedicated teachers. This was particularly important in the first years of independent Lithuania, but later the issue remained quite sensitive. The article analyses teacher education and training system in 1918-1940. An overview of the activities of institutions that prepared teachers (teacher courses, teacher seminaries, educational institute) is given, their curriculum discussed. We also discuss the issues of selection of teachers, their qualifications, salaries and other. The difficulties faced by the education system as a whole and individual teachers are highlighted. Article mostly focuses on primary school teachers, but the issue of secondary school teachers is also discussed to a lesser extent.